Can deliberative democracy work in urban India? - Menon, Sanskriti; Hartz-Karp, Janette; Marinova, Dora (MDPI, 2021)
India faces extensive challenges of rapid urbanization and deficits in human well-being and environmental sustainability. Democratic governance is expected to strengthen public policies and efforts towards sustainability. This article presents a study in Pune, India, which aimed at exploring perceptions about public participation in urban governance and the potential of high-quality public deliberation to meet deficits. The research reveals disaffection of the public with government decision-making and government-led participation. Further, it shows that people are interested in participating in community life and seek to be partners in civic decision-making, but find themselves unable to do so. The study illustrates that high-quality public deliberations facilitated by an independent third party can provide a satisfactory space of participation, learning, and developing balanced outcomes. Citizens expressed readiness for partnership, third-party facilitation, and support from civic advocacy groups. Challenges with regard to government commitment to deliberative democracy will need to be overcome for a purposeful shift from conventional weak to empowered participation of ordinary citizens in civic decision-making. We anticipate that while institutionalization of high-quality public deliberations may take time, civil society-led public deliberations may help raise community expectations and demand for induced deliberative democracy.